Type 2 diabetes patients educated by other patients perform at least as well as patients trained by professionals - Gagliardino, Juan Jose (2013)
Background: Diabetes education can improve the quality of care of people with diabetes, but many organizations are not equipped to manage its implementation. Involving people with diabetes in the education process can overcome the problem. Thus, we compared clinical, metabolic and psychological outcomes in people with type 2 diabetes 1 year after attending a structured diabetes education programme implemented by professional educators versus the same programme implemented by trained peers with diabetes that also provided ongoing peer support. Methods: People with type 2 diabetes (25–75 years) were randomly assigned to attend a 4-week structured diabetes education course delivered by professional educators (control) or previously trained peers (peer). Peers also received continuing psychological support, including examples on how to apply diabetes knowledge in daily life via weekly peer cellular phone calls and bimonthly face-to-face interviews in small groups (ten patients), using a structured questionnaire related to the patient's clinical, metabolic and psychological progress. Identical outcome data from both groups were used for follow-up. Results: Both groups had a comparable positive effect on clinical, metabolic and psychological indicators immediately following the programme. Over the following year, peer-educated subjects had lower A1C and systolic blood pressure and showed higher adherence to physical activity and better control of hypoglycaemic episodes. Conclusion: The non-inferiority of the peer outcomes and the mentioned improvements in this group suggest that volunteer trained peer educators and ongoing support can be successful. This approach provides an effective alternative method of education, especially in areas with limited availability of professionals and economic resources.